Macroeconomic flaws in the IMF’s ‘New’ Institutional view: The case of Brazil - Rafferty, Devin Thomas (Brazilian Keynesian Review, 2017)
In 2012, the IMF issued its ‘New’ Institutional View which endorsed using capital controls for international financial stability, given certain prerequisites. We argue this ‘View’ will be no more successful than the Fund’s other policy predecessors because it mandates solving capital flow-induced macroeconomic imbalances through ‘market-based’ adjustment measures rather than by using capital controls, thus relegating the latter to a secondary role. To present our argument, we use Brazil’s recent history as a proxy for the IMF’s current platform. This is because, despite explicitly not taking advice from the Fund, its actions have been, ironically, nonetheless consistent with the ‘New’ View’s updated prescriptions- which still culminated in crisis. As a result, regardless of the revisions it made in the wake of the Great Financial Crisis, the Fund’s new stance is incapable of averting and stabilizing a crisis; indeed, the case of Brazil suggests it is instead a recipe for creating and amplifying financial macroeconomic fragility.